Human Rights implications of the European Union Migration and Asylum Pact in Search and Rescue Operations - Vella de Fremeaux, Patricia; Attard, Felicity (PEACE & SECURITY-PAIX ET SÉCURITÉ INTERNATIONALES (EuroMediterranean Journal of International Law and International Relations), 2025)
This article focuses on the legal aspects of the search and rescue considerations in the European Union Migration and Asylum Pact. It provides a considered overview of the core instruments making up the European Union Migration and Asylum Pact and considers how these relate to each other and interact with one another. Particular attention is given to the evaluation of the human element in the light of the difficulties surrounding disembarkations following rescue at sea. Building on this legal analysis, the article also highlights the persistent tensions between State sovereignty and the obligation to uphold and respect the principles of international law. The evolving nature of irregular migration places further pressure on legislative frameworks. The authors also reflect on efforts hat aim to operationalize solidarity, while noting that implementation must not come at the cost of weakening obligations under international refugee and human rights law. The authors conclude that, although the Pact represents a positive step in the progressive development of the law in this area, considering the significant efforts made to address migration through cooperation and development, a number of legal and practical challenges remain, which could endanger fundamental human rights protections, therefore continuous monitoring and evaluation is paramount.